The Existence of the Theory of Planned Behaviour: Implications for Purchasing Halal Cosmetics - Eydina Hanni Abdila (Journal of Islamic Economics and Finance Studies, 2025)
Theory of Planned Behaviour (TPB) is a psychological framework used to understand and predict individual behavior. In the context of halal cosmetics, TPB can explain the factors that influence consumer intentions and decisions to purchase these products. Factors such as attitudes towards products, subjective norms, and perceived behavioral control have a major influence on purchasing decisions. With the increasing awareness of the importance of halal-compliant cosmetic products, it is important to understand how TPB can be applied in analyzing consumer behavior in the halal cosmetics market. This research aims to find out how the presence of the Theory of Planned Behavior (TPB) influences consumers' purchases of halal cosmetics. The method used in this research is a qualitative descriptive method with a phenomenological approach. This research includes library research using secondary data obtained from scientific articles and other relevant literature. The findings show that the Theory of Planned Behavior (TPB), which consists of attitudes, subjective norms, and perceived behavioral control, can determine consumer intentions and behavior in purchasing halal cosmetics. This means that the existence of TPB has a big influence on consumers' intentions and behavior to buy halal cosmetics.